Biological and molecular characterization of a basal-Brassica/Raphanus Turnip mosaic virus isolate from Eruca sativa - Ribeiro-Junior, M. R. [UNESP]; Baldini, L. F.S. [UNESP]; Nozaki, D. N. [UNESP]; Cruciol, G. C.D. [UNESP]; Pantoja, K. F.C. [UNESP]; Marchi, B. R. [UNESP]; Moura, M. F. [UNESP]; Pavan, M. A. [UNESP]; Krause-Sakate, R. [UNESP] (Springer Nature, 2018)
Eruca sativa (rocket salad or arugula) and Raphanus raphanistrum (raphanus) plants with mosaic symptoms were found in the field during 2016 in São Paulo State, Brazil. Initially, the plants were submitted to indirect ELISA using a potyvirus antiserum, and then total RNA extraction and RT-PCR were performed using the ELISA-positive samples. The complete coat protein sequence was obtained and the virus was identified as Turnip mosaic virus (TuMV). Biological and Bayesian analysis grouped the TuMV rocket isolate in the Brassica-Raphanus (BR) clade that includes isolates infecting Brassica and Raphanus species. This clade has two sub-clusters, the basal-Brassica/Raphanus (basal-BR) and the Asian-Brassica/Raphanus (Asian-BR), and the rocket isolate was placed in the basal-BR cluster. TuMV from rocket was aphid-transmitted to raphanus and rocket, and sap-transmitted to Chenopodium quinoa, C. amaranticolor, Nicotiana benthamiana, N. tabacum, N. glutinosa, Datura stramonium, Beta vulgaris subsp. vulgaris, Brassica rapa and to seven rocket cultivars, which were heavily affected by the virus. Cabbage and cauliflower were not infected by the virus. According to the phylogenetic analysis, at least two different introductions of TuMV isolates occurred in Brazil, corresponding to the basal-BR and world-B types, infecting Brassica/Raphanus and Brassica, respectively.
Keywords: Raphanus; Rocket; TuMV; Variability